Do Executive Departures to Signal the End of a Scandal Create or Reduce Uncertainty? An Examination of Market Reaction in Stock Option Backdating Scandal Events. Issue 6 (July 2019) - Janney, Jay J.; Gove, Steve
This study examines events at the conclusion of the 2006 stock option backdating scandal: the departures of C-level executives from firms implicated in backdating. The authors ask whether removing executives brings closure to the scandal, or if executive turnover creates greater uncertainty. Using a sample of 236 executive departures, the authors find that although overall market reaction to executive departures is negative, those departures involving a firm's CEO or CFO ameliorate the market reaction. The authors also find that market reaction worsens when the CEO "resigns, " versus being terminated, and when the firm involved has been previously identified as socially responsible. Results suggest that firms, by shaping who and how executives depart, may amplify or dampen the damage of existing scandalizing events.